KIAT PENGEMBANGAN SEKRETARIS PROFESIONAL - Ni Ketut Laswitarni (Forum Manajemen STIMI Handayani Denpasar, 2015)
The era of globalization and advancement of information technologyscience, requires people who cultivate the profession of secretary to always adaptand widen horizons. Level of competence which is now owned secretary needs tobe improved, in order to compete with personnel of secretary to be brought in fromoutside by foreign investors who have the opportunity to do business in Indonesia.Competence trend in these days is the company secretary of the graduates choosesStrata one (S1)/ bachelor.